Solid-state structures and superstructures of two charged donor-acceptor rotaxanes - Zhao, Yanli (2011)
Two [2]rotaxanes and a [2]pseudorotaxane containing 1,5-dioxynaphthalene recognition sites located in the middle of their dumbbell and thread components, respectively, and encircled by single cyclobis(paraquat-p-phenylene) rings have been synthesized under template control and their solid-state (super)structures have been solved. The investigations revealed that the stoppers on the dumbbell components, the solvents, and the counterions can affect the conformations adopted by the [2]rotaxanes and [2]pseudorotaxane in the solid state.